Properties and functionalities offered to foods by edible films and coatings: A review (Research, Society and Development, 2022)
The present study aims to provide an understanding of the properties and functionality of edible films and coatings, in relation to food application conditions, based on a literature review. For this, investigations were carried out in the literature of the last 5 years, using the following keywords: edible film, edible coating, food coating, food film. This review discusses the applications of different edible coatings (carbohydrates, proteins, lipids and composites) as carriers of functional food ingredients capable of improving their quality and shelf life. Edible films and coatings are commonly formulated according to the functional characteristics they provide to the indicated product matrix. In general, the capacity used promotes ecologically correct effects, allowing environmental impact control due to biodegradability, and at the same time allowing its barrier action in the face of food conservation. In addition, they are considered an excellent carrier of ingredients, when bioactive additives are applied, which are able to positively achieve the stability and nutritional value of foods. There are reports of application with aspects of maintenance and quality control for fruits, vegetables, meat and dairy products, since they ensured protection and prolonged storage time. From the study carried out, one can define the need for further research to assess the integrity offered during processing and storage.